Enhancement of biomass and lipid productivity by overexpression of a bZIP transcription factor in Nannochloropsis salina. Issue 2 (3rd November 2017) - Kwon, Sohee; Kang, Nam Kyu; Koh, Hyun Gi; Shin, Sung‐Eun; Lee, Bongsoo; Jeong, Byeong‐ryool; Chang, Yong Keun
Abstract: Microalgae are considered as excellent platforms for biomaterial production that can replace conventional fossil fuel‐based fuels and chemicals. Genetic engineering of microalgae is prerequisite to maximize production of materials and to reduce costs for the production. Transcription factors (TFs) are emerging as key regulators of metabolic pathways to enhance production of molecules for biofuels and other materials. TFs with the basic leucine zipper (bZIP) domain have been known as stress regulators and are associated with lipid metabolism in plants. We overexpressed a bZIP TF, NsbZIP1, in Nannochloropsis salina, and found that transformants showed enhanced growth with concomitant increase in lipid contents. The improved phenotypes were also notable under stress conditions including N limitation and high salt. To understand the mechanism underlying improved phenotypes, we analyzed expression patterns of predicted target genes involved in lipid metabolism via quantitative RT‐PCR, confirming increases transcript levels. NsbZIP1 appeared to be one of type C bZIPs in plants that has been known to regulate lipid metabolism under stress. Taken together, we demonstrated that NsbZIP1 could improve both growth and lipid production, and TF engineering can serve as an excellent genetic engineering tool for production of biofuels and biomaterials in microalgae. Abstract : Transcription factor engineering can serve as an excellent genetic engineering tool in microalgae by regulating multiple enzymes simultaneously. In this study, it was found that NsbZIP1 transcription factor positively regulated expression of ACBP, KAS1, LC‐FACS, and LPAAT which are related to lipid synthesis in Nannochloropsis salina . NsbZIP1‐overexpressing transformants thus increased neutral lipid contents, resulting in increased of FAME production.